The Question of Poverty Alleviation and Environmental Sustainability Through Social Forestry: A Case Study of Mirsarai Sub-District of Bangladesh - Syedul Islam, Mohammed; Nusrat Dooty, Evana (Indian Forester, 2015)
Social Forestry (SF) is viewed as a new idea of forest management instead of traditional management of forest by the Government, by which active participation of the rural people in planning, implementation and benefit sharing of treegrowing schemes is ensured. PROSHIKA, one of the largest non-government organizations in Bangladesh, is working with poor people to bring about their overall development. More particularly, it has launched SF programmes and involved poor members to protect and regenerate forest resources. This paper aims to evaluate the SF program managed by PROSHIKA in Mirsarai sub-district of Bangladesh. Primarily, a socio-economic survey was conducted by interviewing the household head using a semi-structured questionnaire under three specific program components, e.g., strip plantation, agro-forestry and woodlot forestry. Prior to this survey, a participatory rural appraisal (PRA) was also arranged. This study revealed that the mean annual income, household expenditures, and employment opportunity of experimental group were significantly different from that of controlled group, except expenditure on clothing and education. No significant difference for literacy rate was found between experimental and controlled group. Moreover, the hygienic condition among members of experimental group was found better than that of controlled group, which was partly possible due to involvement with PROSHIKA. Finally, the SF project has significantly increased the forest stocks among experimental group in the study area.